Spatial modeling of rain and its relationship to groundwater and the possibility of investing it for agriculture in the district of Afak - Maher Hamood Kadhem (Journal of College of Education, 2022)
ABSTRACTThe study aims to analyze the relationship of rain to groundwater through chemical and physical properties, evaluate it, and the possibility of investing it for agricultural purposes, in addition to the presence of changes in the amount of rain during the studied period (2009 - 2020), especially as it tends to rise in December and gradually decreases in other months during the rainy season, And It was found that there is a correlation between them and it ranged from strong to weak and reached its maximum value in the winter season by (0.78) and its lowest value in the spring and autumn seasons by              (-0.45, -0.14). After evaluating the validity of groundwater through the indicators used in the study, it became clear that most of the wells are ideal for irrigating agricultural crops in the region. A model of spatial suitability of groundwater was built using (GIS - RS) to reach an optimal model spatially. The suitable variety and the medium suitability occupies the largest area for irrigating agricultural lands after they are used optimally, in addition to the practice of permaculture during the rainy season.
Keywords: Spatial modeling , rain, groundwater, agriculture